2017
DOI: 10.1007/s00436-017-5636-2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Toxoplasma gondii and Eimeria tenella co-infection in chickens

Abstract: The widespread apicomplexan parasites Toxoplasma gondii (T. gondii) and Eimeria tenella (E. tenella) are important pathogens with high prevalence in poultry. The aim of our study was the investigation of mutual influences in co-infected chickens, focusing on immune response and course of infection. Two separate trials were performed using in total 96 1-day-old chickens, divided into four study groups: group NC (negative control, uninfected), group PC-T (oral or intramuscular infection with T. gondii oocysts (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 56 publications
2
29
2
Order By: Relevance
“…However, to the best of our knowledge, there is only one published study of Eimeria spp. co-infection with T. gondii [ 19 ] , probably because of the widely assumed sub-clinical character of toxoplasmosis in chickens [ 4 ]. The lack in primary clinical presentation does not necessarily imply that T. gondii infections may not influence the course of other infectious diseases in chickens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, to the best of our knowledge, there is only one published study of Eimeria spp. co-infection with T. gondii [ 19 ] , probably because of the widely assumed sub-clinical character of toxoplasmosis in chickens [ 4 ]. The lack in primary clinical presentation does not necessarily imply that T. gondii infections may not influence the course of other infectious diseases in chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it appears likely that simultaneous appearance of these two apicomplexan parasites may affect the reaction of host macrophages to parasite infection. Experimental in vivo studies revealed a partial mutual interaction between T. gondii and E. tenella [ 19 ] in chickens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normally, the ratio of Th1/Th2 is in dynamic balance, which may be disrupted by specific antigen stimulation and results in a drift of Th1/Th2 cell subsets. IFN-γ can promote the differentiation of Th0 into Th1 cells, while IL-4 is necessary for the differentiation of Th2 cells [36,37]. Compared with control group S. japonicum infection dramatically increased the serum IFN-γ levels of the hosts.…”
Section: Structure Succession Analysis Of Gut Microbiota Community Comentioning
confidence: 95%
“…In spite of high seroprevalence rates reported for both T. gondii and E. tenella in chickens, little is known to date about the mutual interplay between these two parasites, particularly during host cell invasion. Experimental in vivo and ex vivo co-infection models in chicken macrophages were established recently and thus suitable tools are now available for further co-infection studies [19,20].…”
mentioning
confidence: 99%